The Effectiveness Bits and Pieces Game to Student Writing Skill and Seventh Grade Student - Wahyuni, Alfika; Fatkurrochman, Henri; Mardiyana Devanti, Yeni (ENJEL: English Journal of Education and Literature, 2024)
In this research, students had problems in writing a text, the difficulty of generating ideas to be written was the main obstacle. This research aims to determine whether the Bits and Pieces Game is effective for the writing skills of class VII students of SMP Muhammadiyah 1 Jember. This study used a quasi-experimental pre-test and post-test method with a non-equivalent control group design. The population in this study were all class VII students of SMP Muhammadiyah 1 Jember for the 2022/2023 academic year. Using saturated sampling technique (total sampling) which involved all students of class VII with a total of 36 students, then divided into two groups, there were class VII A with 22 students as the control group and VII B with 14 students as the experimental group. Both classes were given pre-test and post-test. The results of his research showed that the control class was from 45.63 to 52.45, and the experimental class was from 56.42 to 74.43. From the hypothesis test, it is obtained that the significance of the T-test Sig 0.000 <0.05, which means the null hypothesis (Ho) is rejected. This shows that the Bits and Pieces Game has a significant effect on students' writing skills.